2019
DOI: 10.1108/jima-02-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

A study of customers’ perception of Islamic banking in Oman

Abstract: Purpose The concept of Islamic banking (IB) as a discipline and the introduction of the full-fledged Islamic banks and Islamic windows are relatively newer developments in the banking sector in Oman. This paper aims to assess customers’ perceptions of the Islamic banks and IB windows in Oman. Design/methodology/approach Following the interpretive paradigm and an exploratory research design, data collected through personal interviews with a group of 60 respondents in two of the prominent cities in Oman were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…Consequently, research on Islamic finance has sharply accelerated within the past two decades, first in management, finance, and economics (see, Al Rahahleh et al 2019;Ayub 2018;Fang 2014;Khan and Bhatti 2008a;Kurpad 2016) and more recently, in international business and marketing literature (see, Belwal and Maqbali 2019;Butt et al 2018;Fang 2016;Amin et al 2014;Khaliq et al 2011). Despite its robustness, the literature on Islamic finance remains fragmented, offering little guidance for researchers attempting to conceptualize the marketing strategies of Islamic finance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research on Islamic finance has sharply accelerated within the past two decades, first in management, finance, and economics (see, Al Rahahleh et al 2019;Ayub 2018;Fang 2014;Khan and Bhatti 2008a;Kurpad 2016) and more recently, in international business and marketing literature (see, Belwal and Maqbali 2019;Butt et al 2018;Fang 2016;Amin et al 2014;Khaliq et al 2011). Despite its robustness, the literature on Islamic finance remains fragmented, offering little guidance for researchers attempting to conceptualize the marketing strategies of Islamic finance.…”
Section: Introductionmentioning
confidence: 99%
“…Islamic banks are defined as "A system of banking or banking activities that is consistent with the principles of the Shari'ah (Islamic rulings) and its practical application through the development of Islamic economics" (Belwal & Al Maqbali, 2018). Islamic banks are not using the interest system on each transaction but with the term profit sharing.…”
Section: The Intention Of Switching Islamic Bankmentioning
confidence: 99%
“…Several previous studies have proven that religiosity has a linear and significant relationship to consumer attitudes on Islamic banks (Abou-Youssef et al, 2015), consumer attitudes on Muslim fashion trends(Riptiono, 2019). The other literature also proves that there is a positive relationship between religiosity of consumer intentions on Islamic products such as halal banking products (Butt & Aftab, 2013), halal products(Nurhayati & Hendar, 2019), consumer choice toward Islamic banks(Belwal & Al Maqbali, 2018). Therefore, the hypotheses tested are:H5: Religiosity has a significant effect on consumer attitude toward Islamic bank.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, despite this encouraging success, Islamic bank has been viewed as less popular and less experienced as compared to the conventional banks (Suhartanto, 2019). Not only that, studies also have shown that there are still consumers who are unaware of the differences between the concept of an Islamic bank as compared to its conventional counterparts (Al-Tamimi, Lafi, & Uddin, 2009;Belwal & Al Maqbali, 2019;Kaakeh, Hassan, & van Hemmen Almazor, 2018;Souiden & Rani, 2015). This is applicable not only among Muslim customers, but also among non-Muslim target markets, as Mohamad and Majid (2016) claimed that non-Muslim customers are aware of the Islamic bank but have low knowledge and understanding on the concept.…”
Section: Introductionmentioning
confidence: 99%